Assessing the Adjuvant Efficacy of Oral Gabapentin to Balanced Anaesthesia for Elective Surgeries in Dogs - Rajesh, Chendurpandi; Vishnugurubaran, Dhanakaran; Jayakumar, Kulandaivel; Vijayakaran, Karunakaran; Kaarthick, Damodaran; Thabsheera, Adiyattil (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Oral gabapentin has been increasingly explored for its anaesthetic sparing properties in veterinary anesthesia. This study aimed to  evaluate the efficacy of oral gabapentin as an adjunct in balanced anaesthesia in dogs undergoing elective surgeries, with a focus on  its reduction in anaesthetic requirements. A total of 20 dogs brought for elective surgeries were selected and the selected animals  were divided into two groups of 10 animals each, viz., group I and group II. Group II animals received oral gabapentin (10 mg/kg) as  premedicant twice a day for two days before the surgery and one dose, 2 h before the surgery. Both groups were pre-medicated with  dexmedetomidine and butorphanol, followed by induction with diazepam and ketamine and maintenance with isoflurane. Isoflurane  concentrations were measured continuously during the surgical procedure. The gabapentin group showed a significant reduction in  isoflurane requirements compared to the control group (p
Keywords: Balanced anesthesia; Dog; Elective surgeries; Gabapentin; Isoflurane